Investigating mutations in the genes GDF9 and BMP15 in Pelibuey sheep through the amplification-refractory mutation system with tetra-primers - Muñoz-García, Canuto; Segura-León, Obdulia L.; Gómez-Vargas, Julio C.; González-Maldonado, Juan; Quintero-Elisea, Juan A.; Martínez-Montoya, Juan F.; Cortez-Romero, César (Austral Journal of Veterinary Sciences, 2023)
Single Nucleotide Polymorphisms (SNP) or mutations are variations with a broad distribution in the genome and, as part of genetic studies, SNP allow the identification of allelic variants related to characteristics of economic importance in sheep production. However, the identification of SNP and their genotypes through sequencing is expensive, as it requires specialized materials and equipment. The objective of this study was to identify polymorphisms and their genotypes in the growth differentiation factor 9 (GDF9) and bone morphogenetic protein 15 (BMP15) genes in Pelibuey sheep using the tetra-primer amplification-refractory mutation system through polymerase chain reaction (T-ARMS-PCR). DNA extraction and amplification of BMP15 and GDF9 were conducted from blood samples contained in WhatmanTM FTATM cards from 60 multiparous Pelibuey ewes with reproductive records. The T-ARMS-PCR methodology allowed the identification of wild-type genotypes and mutated homozygous genotypes in polymorphisms G4 and G6 of GDF9, whereas mutations in the BMP15 gene were not found. These results were confirmed by sequencing. In conclusion, the T-ARMS-PCR methodology allowed the identification of mutated and wild-type genotypes in SNP G4 and G6 of GDF9, although no mutations were found in BMP15 in Pelibuey sheep. This technique was found to be reliable, rapid, and easily applied to identify polymorphic genotypes.